Microblade technology and site structure of the Late Mesolithic hunter-gatherers in Donggi-Cona Lake Basin: new implications for human dispersals and interactions in the northeastern Tibetan Plateau during the Holocene. (10th February 2021) - Chen, Youcheng; Hou, Guangliang; Gao, Jingyi; E, Chongyi; Chen, Xiaoliang; Lancuo, Zhuoma
Abstract: The high-resolution tracing of the behavior pattern and lithic technology of the last hunter-gatherers in the Tibetan Plateau (TP) has been a rarely worked area. Here we report four Late Mesolithic sites comprised of both base camp and temporary localities in the Donggi-Cona Lake Basin with the elevations exceeding 4000 m above sea level, among which DJCN 3-2-2 was well preserved with organized site structure and dated to ca. 5400-5000 cal BP. We analyze the microblade technology and site structure in the Donggi-Cona Lake Basin and discuss it in the context of the prehistory of China. The Donggi-Cona microblade sites provide significant insights into the technology, behavior, and social organization of the last Mesolithic hunter-gatherers in the TP, and into the human dispersals and interactions in the northeastern Tibetan Plateau during the Holocene.